2012
DOI: 10.1002/chem.201202074
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective 1,4‐ and 1,6‐Addition of P(O)H Compounds to p‐Quinones: A Divergent Method for the Synthesis of C‐ and O‐Phosphoryl Hydroquinone Derivatives

Abstract: The reaction of P(O)-H compounds with p-quinones could proceed through either 1,4- or 1,6-addition pathways by employing different additives to selectively give the corresponding C- and O-phosphoryl hydroquinone derivatives in good yields. Oxidative double 1,4-addition of P(O)-H compounds to p-quinones was also achieved by tuning the solvent, affording a facile synthesis of bis-substituted hydroquinones with phosphorus functionality. Further studies on these reactions by using optically active H-phosphinates s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 74 publications
1
20
0
Order By: Relevance
“…The similar reported reaction using 1,4-benzoquinone supports the reaction path. 35 Partial disubstitution in the obtained EtPhosPANIs 3 is expected from these results. The chemical shi of phosphorus in 31 P NMR of 6 and 7 were 20.1 and 18.8 ppm, respectively.…”
Section: Synthesismentioning
confidence: 58%
“…The similar reported reaction using 1,4-benzoquinone supports the reaction path. 35 Partial disubstitution in the obtained EtPhosPANIs 3 is expected from these results. The chemical shi of phosphorus in 31 P NMR of 6 and 7 were 20.1 and 18.8 ppm, respectively.…”
Section: Synthesismentioning
confidence: 58%
“…Recently, we successfully synthesized optically active Cand O-phosphoryl hydroquinone derivatives through selective 1,4-and 1,6-additions of P-chiral P(O)-H bonds to pquinones under mild conditions. 17 This reaction proceeded stereospecifically. The structures of the products were determined by X-ray analysis, confirming that the configuration at phosphorus was unchanged during the reaction process.…”
Section: Addition To P-quinonesmentioning
confidence: 93%
“…A mechanistic study revealed that this oxidative double 1,4-addition of P(O)-H compounds to p-quinones proceeds through a simultaneous double 1,4-addition and subsequent oxidation process, rather than the generally accepted stepwise 1,4-addition/oxidation sequence. 17 Scheme 12 Stereospecific oxidative double 1,4-addition of phenylphosphinate (R P )-1c to p-quinone However, in the presence of triethylamine, the reaction of phenylphosphinate (R P )-1c with p-quinones proceeded through a stereospecific 1,6-addition path to give the optically active O-phosphoryl substituted hydroquinone derivatives (S P )-9 (Scheme 13).…”
Section: Addition To P-quinonesmentioning
confidence: 99%
“…[20] The P-vinylbenzyls derivatives of 4-vinylbenzyl chloride are known molecules and have been described in the literature. [8,13,[15][16][17][18][19][20]23] Some of them are commercially available. [23] However, no analog example with P-CH 2 fragment in ortho or meta position compared to the vinyl group has been reported.…”
Section: Introductionmentioning
confidence: 99%